Early Outcome of Laparoscopic Abdominoperineal Resection, Our Experience in Bangabandhu Sheikh Mujib Medical University (Faridpur Medical College Journal, 2014)
Anorectal malignancies that require abdominoperineal resection (APR) is very common. Laparoscopic APR can be a better option. Laparoscopic APR has been seldom studied. This study aims to evaluate perioperative and early postoperative outcomes of laparoscopic APRs performed for the treatment of ano-rectal carcinomas. Patients operated for ano-rectal carcinoma between June 2011 to June 2013 in Bangabandhu Sheikh Mujib Medical University (BSMMU) were observed. Demographics, tumor and procedure-related parameters, perioperative results, early postoperative outcomes and survival were observed. Total 22 patients were under went laparoscopic APR. Male: Female ratio was 15:7 (68.18%: 31.82%). Age range was from 30-65 years with a mean age of 36.55 years. Mean operation time was 165 minutes and mean post-operative hospital stay was 6.8 days. Overall complication rate was 45.45%. Laparoscopic APR is a safe, effective and technically feasible procedure. It can be a better operative procedure than open APR. DOI: http://dx.doi.org/10.3329/fmcj.v8i2.20281 Faridpur Med. Coll. J. 2013;8(2): 53-55